I Found a Democratic School, Finally: A Response to “This is What Democracy Looks Like: Some Thoughts on Democratic Schools” - Gary Weilbacher (Middle Grades Review, 2020)
This article is a response to “This is What Democracy Looks Like: Some Thoughts on Democratic Schools” by James A. Beane, published in Volume 5, Issue 3 of the Middle Grades Review. The article provides a brief description of the author’s time in a private community school founded on democratic practices. He also recalls the interest in democratic schooling instilled by the 1990s movement tied to integrative curriculum. The author believes that it is time to revisit conversations around democratic schools and is hopeful that Beane’s article can help stimulate those discussions.
Keywords: democratic schools; integrative curriculum